DETERMINANTS OF FRAUD PREVENTION MANAGEMENT GRANT FUNDING FINANCE: (Study of Jambi Province Bawaslu and Regency/City Bawaslu in Jambi Province) - Astrina, Herwinda; Rahayu, Sri; Kusumastuti, Ratih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The management of direct grant funds for regional elections requires streamlined processes within the Provincial Election Supervisory Agency and Regency/City Election Supervisory Committees. Technical Instructions outlined in a 2019 decree guide work plans, budgets, administration, accountability, and reporting. Efforts to prevent fraud in grant management are essential for reliable financial reporting, operational efficiency, auditor confidence, legal compliance, and asset protection. Controls, whether preventive or detective, manual or automatic, play a crucial role in these efforts. This research aims to analyze the Determinants of Fraud Prevention in Financial Management of Grant Funds. The context chosen was the Bawaslu of Jambi Province and the Bawaslu of Districts/Cities throughout Jambi Province, totaling 65 people. The analytical tool used in this research is SMART PLS. The results can be concluded that the competency of the work unit apparatus has no effect on preventing fraud in the financial management of grant funds, the internal control system has an effect on preventing fraud in the financial management of grant funds, Whistleblowing systems have an effect on preventing fraud in the financial management of grant funds.